Retrospective Study of Craniovertebral Junction (CVJ) Anomalies: A Clinical Profile and Outcome Analysis of Surgically Treated Patients - Paudel, Prakash; Khadka, Nilam K; Shrestha, Dipak; Bista, Prakash; Sharma, Gopal R (Nepal Journal of Neuroscience, 2019)
Craniovertebral junction (CVJ) is a complex anatomic region providing stability and mobility to the most important part of the craniospinal axis. The purpose of this study is to analyse clinical characteristics and outcome after surgical management of patients with CVJ anomalies presented to Neurosurgery department, Bir hospital Kathmandu Nepal. A retrospective analysis of 21 patients, managed surgically for craniovertebral instability between 2013 and 2017, was performed. Imaging studies were reviewed for bony and soft tissue details. Patients managed with posterior approach alone (either occipitocervical fusion or C1-2 fusion with or without bony decompression) were included in the study. Outcome was assessed by comparing pre and post operative Nurick grade. Most common causes of CVJ instability were non union of old odontoid fracture (38.1%)and OsOdontoidium (38.1%). 76.2% had intramedullary high signal intensities in T2 weighted MRI while 90% had cervicomedullary compression. Pre operatively, 52.38% had Nurick grading scale of 4 to 5 while 47.62%had 0-3 Nurick grade scale. Post operatively, 71.42% improved clinically, 23.80% remained unchanged while one patient deteriorated. Mean duration of follow up was 20.87 months (6-60 months). Pre operative Nurick grade was significantly associated with post operative outcome (p=0.042). Early surgical intervention is associated with better clinical outcome. Larger prospective study with clinical and radiological follow up is recommended.